Molecular Biomarker of Drug Resistance Developed From Patient-Derived Organoids Predicts Survival of Colorectal Cancer Patients - Chen, Lifeng; Tian, Bo; Liu, Wen; Liang, Haitao; You, Yong; Liu, Weizhen (Frontiers in Oncology, 2022)
5-fluorouracil (5-Fu) is the critical composition of colorectal cancer (CRC) treatments. Prognostic and predictive molecular biomarker for CRC patients (CRCpts) treated with 5-Fu based chemotherapy can provide assistance for tailoring treatment approach. Here, we established a molecular biomarker of 5-Fu resistance derived from CRC organoids (CRCOs) for predicting the survival of CRCpts. 41 CRCOs cultures were generated from 50 CRC tumor tissues after surgery (82%). Following experiments revealed a great diversity in drug sensitivity for 10 μM 5-Fu treatment tested by using organoid size change. Fourteen cases (34.1%) were 5-Fu sensitive and the other twenty-seven (65.9%) were resistant. Then differentially expressed genes (DEGs) associated with 5-Fu resistance were outputted by transcriptome sequencing. In particular, DEGs were generated in two comparison groups: 1) 5-Fu sensitive and resistant untreated CRCOs; 2) CRCOs before 5-Fu treatment and surviving CRCOs after 5-Fu treatment. Some molecules and most of pathways that have been reported to be involved in 5-Fu resistance were identified in current research. By using DEGs correlated with 5-Fu resistance and survival of CRCpts, the gene signature and drug resistant score model (DRSM) containing five molecules were established in TCGA-CRC cohort by LASSO regression analysis and 5-fold cross validation. Multivariate analysis revealed that DRS (drug resistant score) was an independent prognostic factor for OS (overall survival) in CRCpts in TCGA-CRC cohort (P < 0.001). Further validation results from four GSE cohorts elucidated that the DRSM based on five genes related to 5-Fu chemosensitivity and developed from patient-derived organoids can predict survival of CRCpts. Meanwhile, our model could predict the survival of CRCpts in different subgroups. Besides, the difference of molecular pathways, tumor mutational burden (TMB), immune response related pathways, immune score, stromal score and immune cell proportion were dissected between DRS-high and DRS-low patients in TCGA-CRC cohort.